Brief Report: Systemic Inflammation, Immune Activation, and Impaired Lung Function Among People Living With HIV in Rural Uganda. (15th August 2018) - North, Crystal M.; Muyanja, Daniel; Kakuhikire, Bernard; Tsai, Alexander C.; Tracy, Russell P.; Hunt, Peter W.; Kwon, Douglas S.; Christiani, David C.; Okello, Samson; Siedner, Mark J.
Abstract : Background: Although both chronic lung disease and HIV are inflammatory diseases common in sub-Saharan Africa, the relationship between systemic inflammation and lung function among people living with HIV (PLWH) in sub-Saharan Africa is not well described. Methods: We measured lung function (using spirometry) and serum high sensitivity C-reactive protein, interleukin 6 (IL-6), soluble CD14 (sCD14), and soluble CD163 (sCD163) in 125 PLWH on stable antiretroviral therapy (ART) and 109 age- and sex-similar HIV-uninfected control subjects in rural Uganda. We modeled the relationship between lung function and systemic inflammation using linear regression, stratified by HIV serostatus, controlled for age, sex, height, tobacco, and biomass exposure. Results: Half of subjects [46% (107/234)] were women, and the median age was 52 years (interquartile range: 48–55). Most PLWH [92% (115/125)] were virologically suppressed on first-line ART. Median CD4 count was 472 cells/mm 3 . In multivariable linear regression models stratified by HIV serostatus, an interquartile range increase in IL-6 and sCD163 were each inversely associated with lung function (mL, 95% confidence interval) among PLWH [IL-6: forced expiratory volume in 1 second (FEV1 ) −18.1 (−29.1 to −7.1), forced vital capacity (FVC) −17.1 (−28.2 to −5.9); sCD163: FVC −14.3 (−26.9 to −1.7)]. High sensitivity C-reactive protein (>3 vs. <1 mg/L) was inversely associated with lung function among both PLWH and HIV-uninfected control subjects [PLWH: FEV1 −39.3 (−61.7 to −16.9), FVC −44.0 (−48.4 to −6.4); HIV-uninfected: FEV1 −37.9 (−63.2 to −12.6), FVC −58.0 (−88.4 to −27.5)]. sCD14 was not associated with lung function, and all interaction terms were insignificant. Conclusions: Macrophage activation and systemic inflammation are associated with lower lung function among PLWH on stable ART in rural Uganda. Future work should focus on underlying mechanisms and public health implications. Abstract : Supplemental Digital Content is Available in the Text.